Global research landscape of ferroptosis in gastric cancer: a multidisciplinary bibliometric analysis based on multiple databases (2017-2025) - Ji, Nianshan; Cheng, Yiyao; Peng, Yuheng; Sun, Zhiguang (Frontiers in Immunology, 2026)
ObjectiveFerroptosis, an iron-dependent regulated cell death mechanism, has recently gained attention for its crucial role in tumor progression and immune regulation. Gastric cancer (GC), one of the most common and deadly malignancies worldwide, remains a major clinical challenge. This study aims to systematically analyze the global research landscape, hotspots, and trends of ferroptosis in gastric cancer from 2017 to 2025, with a focus on its immunological implications.MethodsPublications related to ferroptosis and gastric cancer published between January 1, 2017 and April 22, 2025 were retrieved from the Web of Science Core Collection (WoSCC) and Scopus databases (n = 974). Bibliometric and visualization analyses were performed using R software (bibliometrix package), VOSviewer, and CiteSpace to explore publication trends, collaboration patterns, keyword co-occurrence, and thematic evolution.ResultsResearch output showed a continuous upward trend, with China leading in publication volume, followed by the United States, Japan, Canada, and South Korea. Frontiers in Pharmacology and Frontiers in Oncology were the most productive journals, while Cell and Nature were the most frequently cited. The most prominent themes included “immune checkpoint,” “tumor immune microenvironment,” “ferroptosis mechanisms,” “drug resistance,” and “non-coding RNAs.” Notably, the STAT3–ferroptosis axis and immune pathways were identified as key translational targets.ConclusionFerroptosis has become an important research frontier in gastric cancer and is increasingly recognized as a promising therapeutic strategy to modulate the tumor immune microenvironment and enhance immunotherapy efficacy. This study provides a comprehensive overview of the global research landscape, offering valuable guidance for future studies in cancer immunology and ferroptosis-based therapy.